Niko IDENTIFIKASI RAGAM HIAS ACEH PADA ILUMINASI MUSHAF AL-QURAN KUNO KOLEKSI PEDIR MUSEUM - Niko Andeska; Indra Setiawan; Rika Wirandi (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
Illumination or manuscript (the art of the book), can be interpreted as a decorative visual work that is containedin the manuscript that serves as a decoration. Basically used to beautify certain parts, especially on thefront page of the script (frontispiece). In ancient manuscripts by Acehnese scholars, various forms of illuminationwere adopted which adopted the local Acehnese decorative style. The beauty of the illumination in thetreasures of ancient manuscripts by Acehnese ulama, especially those contained in the Al-Quran Manuscriptscompiled into a collection of non-governmental institutions (private) in the city of Banda Aceh at this time hasnot been fully touched by studies that lead to visual aspects. Both in terms of comprehensive data collectionto in-depth analysis in the perspective of fine arts. This study aims to examine the visual aspects that focus onthe variety of Aceh’s decoration on illuminations in several Al-Quran Manuscripts from the Pedir Museumcollection. This research uses quantitative research methods, using data collection techniques through observation,interviews, documentation, and data collection. The data that has been collected is then carried out theprocess of identifying, categorizing, and analyzing the data by using the digitizing method of ornamentaldiversity in several Al-Quran Manuscripts from the Banda Aceh Pedir Museum collection.